Microgreens: Consumer sensory perception and acceptance of an emerging functional food crop. Issue 4 (6th March 2020) - Michell, Kiri A.; Isweiri, Hanan; Newman, Steven E.; Bunning, Marisa; Bellows, Laura L.; Dinges, Michelle M.; Grabos, Lauren E.; Rao, Sangeeta; Foster, Michelle T.; Heuberger, Adam L.; Prenni, Jessica E.; Thompson, Henry J.; et al.
Abstract : Abstract: Microgreens are an emerging functional food crop with promise for sustainably diversifying global food systems, facilitating adaptations to urbanization and global climate change, and promoting human health. Previous work suggests microgreens have high nutritional quality, low environmental impacts, and broad consumer acceptance. For better reception into the global food system and increased per capita consumption, research is needed to elucidate consumer acceptance of various microgreens species, including factors contributing to their acceptance or lack thereof. Using a consumer panel ( n = 99), this study evaluated consumer sensory perception and acceptability of six microgreens species (arugula, broccoli, bull's blood beet, red cabbage, red garnet amaranth, and tendril pea), and potential drivers and barriers to consumer acceptance. All microgreens species received high mean liking scores for acceptability by consumers (means ranged from highly acceptable to slightly acceptable), with more distinct differences across microgreens species for flavor and overall acceptability, which appeared to be driven by specific sensory properties. Data from principal component analysis demonstrated that high acceptability scores were associated with higher intent to purchase microgreens and negatively associated with food neophobia. Participants indicated that factors such as knowledge and familiarity of microgreens, cost, access/availability, freshness/shelf life, among other factors, influence their intention to purchase microgreens. These findings suggest that further integration of microgreens into the global food system will be met with high consumer acceptability, but needs to be aligned with enhanced consumer education regarding microgreens, as well as considerations of cost, availability/access, and freshness/shelf life. Practical Application: Researchers investigated consumer sensory perception and acceptability of six microgreens species (arugula, broccoli, bull's blood beet, red cabbage, red garnet amaranth, and tendril pea), and potential drivers and barriers to consumer acceptance. All microgreens tested had high consumer acceptability, but certain factors such as sensory perception and food neophobia impacted their acceptability. Additionally, participants indicated that factors such as knowledge, access and availability, cost, freshness, and shelf life may impact the purchasing of microgreens and thus are important factors to consider for further integration of this emerging functional food crop into the global food system.